Evaluation of the construction level and analysis of the spatio–temporal evolution pattern of ecological civilization in the Yellow River Basin - Danyang FENG; Xiaojie MENG; Ranran YANG; Yingying CHAI; Yuefeng SHI; Mengyang GAO (Sustainable Futures)
The evaluation of ecological civilization is an effective tool for measuring a country's level of sustainable development. A comprehensive evaluation indicator system was constructed for the ecological civilization construction level (ECCL) in China's Yellow River Basin, encompassing ecology and environment, green economy, green life, and institution and culture. The spatio‒temporal dynamic entropy weight TOPSIS method was used for weighting, and the spatial pattern and temporal evolution of the ECCL and its influencing factors in the river basin were quantitatively analysed. The ecological civilization index (ECI) in the nine provinces (regions) of the Yellow River Basin from 2010 to 2022 exhibited an overall improvement trend and fluctuated upward, with the largest increase from 2016 to 2022, of which Qinghai, Sichuan, and Shaanxi Provinces occurred at the leading construction level. The overall degree of coupling coordination between the subsystems changed from low‒level to favourable, with the degree of coordination in Qinghai and Shaanxi steadily increasing, and that in Gansu rapidly developing. The spatial correlation in various provinces (regions) in the Yellow River Basin fluctuated and increased, but the overall synergy was insufficient, with Sichuan and Qinghai demonstrating relatively high correlations. The most significant factors influencing the ECCL in the river basin were ecological quality, environmental quality, and energy conservation and carbon reduction, among which the proportion of surface water quality at/above Grade III, the proportion of water quality below Grade V, the forest coverage rate, the proportion of nonfossil fuels in the total primary energy consumption and ecological index greatly impacted the spatial distribution.